The geographic scope of environmental problems and the impact of internal support on the success of local interventions of international NGOs: The case of Greenpeace - Plourde, Yves (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2022)
This study examines how internal support benefits the local interventions of international environmental NGOs. It addresses this question by examining 102 cases of interventions conducted by 5 Greenpeace national organizations in Europe. The results indicate that the benefits of internal support partially depend on the geographic scope of the environmental problems targeted by the NGO. While interventions that focus on international problems generally benefit from internal support, interventions that focus on local problems are generally more successful without support. Implications for the resource allocation decisions of international NGOs and for the generalizability of international management theories are discussed.